Modelo Conceptual de los Marcos Primarios de la Experiencia Turística Mediada por Tecnología. Ilustración a Partir de Recorridos Subacuáticos en Cozumel, México / Conceptual Model of Primary Frames on Tourist Experience Mediated by Technology. Illustration from Subaquatic Tours in Cozumel, Mexico - Gonzalez Damian, Alfonso; Macias Ramirez, Alma Rosa (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2017)
Se propone un modelo conceptual para la comprensión de la forma en la que se construye socialmente la experiencia de viaje turístico en presencia de tecnologías de información y comunicación. La finalidad es que este modelo aporte un marco para la comprensión respecto a la forma en la que se consideraría la experiencia turística colectivamente enriquecida. Como fundamento del modelo se aplica el concepto de marco de experiencia primario propuesto por Erving Goffman, adaptado a la interacción entre turistas y anfitriones, mediada por la presencia de la tecnología. Se realizó observación participativa y entrevistas de tipo abierto a turistas en Cozumel, México, específicamente centrados en los recorridos turísticos subacuáticos en el parque marino. La información obtenida fue sistematizada y objeto de análisis de contenido cualitativo, con asistencia del software Atlas-ti. A partir de los hallazgos se desarrolló el modelo conceptual, se exploraron sus limitaciones y posibilidades analíticas, así como las futuras líneas de investigación tanto a nivel teórico como aplicado. PALABRAS CLAVE Experiencia Turística. Turista y Anfitrión. Tecnología. Modelo Conceptual. Cozumel, México. ABSTRACT A conceptual model is proposed for understanding the way that tourist experience is socially constructed in presence of informational technology and communication. The purpose for this model is to provide a framework for understanding how tourist experience would be considered as collectively enriched. The concept of primary experience framework proposed by Erving Goffman is applied and it was basis for the model adapted to the interaction between tourists and hosts, mediated by the presence of technology. Participant observation and open-ended interviews tourists in Cozumel, Mexico, were conducted, applied to a subaquatic tour in which use was made of underwater cameras capable of WIFI connectivity. The information obtained was systematized and subject to qualitative content analysis, with the assistance of Atlas-ti software. From findings the conceptual model was developed, its limitations and analytical possibilities, as well as future research both theoretical and applied were explored. KEYWORDS Tourist Experience. Tourist and Host. Technology. Conceptual Model. Cozumel, Mexico. AUTORES Alfonso González-Damián – Doutor. Profesor investigador, Universidad de Quintana Roo, Cozumel, México. Orcid iD: http://orcid.org/0000-0003-4396-0100. E-mail gonzalezd@uqroo.edu.mx Alma Rosa Macías Ramírez - Maestra. Profesora investigadora, Universidad de Quintana Roo, Cozumel, México. Currículo: https://www.researchgate.net/profile/Alma_Ramirez5 E-mail: maciasalma@uqroo.edu.mx REFERENCIAS Araújo P.O., Dos Santos, M. M.C. & Pereira, S. (2013). Dimensión relacional de la acogida. Estudios Y Perspectivas En Turismo, 22(1), 138-153. Baptista, I. (2008). Hospitalidade e eleição intersubjectiva: sobre o espírito que guarda os lugares. Revista Hospitalidade, 5(2), 5-14. Baudrillard, J. (1975). El espejo de la producción. Madrid: Gedisa. Berger, P. L. & Luckmann, T. (1991). The social construction of reality: A treatise in the sociology of knowledge. St. Ives, USA: Penguin Books. Bitner, M. J., Booms, B.H. & Tetreault, M. (1990). The service encounter: diagnosing favorable and unfavorable incidents. Journal of Marketing, 5(1), 71-84. Boorstin, D. J. (1964). The Image: a guide to pseudo-events in America. New York: Vintage Books. Buhalis, D. & Amaranggana, A. (2013). Smart tourism destinations. In Z. Xiang & I. P. Tussyadiah (Eds.), Information Communication Technologies in Tourism 2014. Springer. Buhalis, D. & Law, R. (2008). Progress in information technology and tourism management: 20 years on and 10 years after the Internet-The state of eTourism research. Tourism Management, 29(4), 609-623. doi:10.1016/j.tourman.2008.01.005 Buhalis, D. & O’Connor, P. (2005). Information communication technology revolutionizing tourism. Tourism Recreation Research, 30(3), 7-16. Cáceres, P. (2003). Análisis cualitativo de contenido: Una alternativa metodológica alcanzable. Psicoperspectivas. Individuo y Sociedad, 2(1), 53-82. Dos Santos, M. M.C. & Araújo P., O. (2012). Hospitalidade numa perspectiva coletiva : O corpo coletivo acolhedor. Revista Brasileira de Pesquisa em Turismo, 6(1), 3–15. Cohen, E. (1979). A phenomenology of tourist experiences. Sociology, 13(2), 179-201. doi: 10.1177/003803857901300203 Diener, E. & Diener, M. (2009). Cross-cultural correlates of life satisfaction and self-esteem. Journal of Personality and Social Psychology, 68, 653-663. Edensor, T. (2011). Entangled agencies, material networks and repair in a building assemblage: The mutable stone of St Ann’s Church, Manchester. Transactions of the Institute of British Geographers, 36(2), 238-252. doi:10.1111/j.1475-5661.2010.00421.x Egger, R. (2010). Theorizing Web 2.0 phenomena in tourism: a sociological signpost. Information Technology & Tourism, 12(2), 125-137. doi:10.3727/109830510X12887971002666 Elands, B. H. M. & Lengkeek, J. (2012). The tourist experience of out-there-ness: Theory and empirical research. Forest Policy and Economics, 19, 31-38. doi:10.1016/j.forpol.2011.11.004 Ewart, A. (1989). Outdoor adventure pursuits: foundations, models and theories. Columbus, Ohio: Publishing Horizons. Elliott, R. & Boshoff, C. (2009). The marketing of tourism services using the internet: A resource-based view. South African Journal of Business Management, 40(3), 35-49. Gibson, H. & Yiannakis, A. (2002). Tourist roles, needs and the life course. Annals of Tourism Research, 29(2), 358-383. Goffman, E. (1974). Frame analysis: An essay on the organization of experience. Cambridge: Harvard University Press. González D., A. (2004). <a href="https://www.researchgate.net/profile/Alfonso_Damian/publication/237089501_El_anfitrin_como_actor_social_en_el_turismo._Reflexiones_desde_el_caso_de_Ixtapan_de_la_Sal_Mxico/links/0046352ebe7a43b498000000.pdf">El anfitrión como actor social en el turismo. Reflexiones desde el caso de Ixtapan de la Sal, México. Revista de Ciencias Sociales (CR), 3(105), 155-168. González D., A. (2009). El turismo desde un enfoque de sociología constructivista. Teoría Y Praxis, 6, 107-122. González D., A. (2011). Construcción social del turismo. Una perspectiva teórica de sociología constructivista para el estudio del turismo. Saarbrücken: Editorial Académica Española. Govers, R. (2005). Virtual tourism destination image: Glocal identities constructed, perceived and experienced. Rotterdam: Erasmus Research Institute of Management. Gretzel, U., Fesenmaier, D. R., Formica, S. & O’Leary, J. T. (2006). Searching for the Future: Challenges faced by destination marketing organizations. Journal of Travel Research, 45(2), 116-126. doi:10.1177/0047287506291598 Gretzel, U., & Jamal, T. (2009). Conceptualizing the creative tourist class: Technology, mobility, and tourism experiences. Tourism Analysis. 14(4), 471-481. doi: 10.3727/108354209X12596287114219 Guttentag, D. a. (2010). Virtual reality: Applications and implications for tourism. Tourism Management, 31(5), 637-651. doi:10.1016/j.tourman.2009.07.003 Havitz, M. & Dimanche, F. (1990). Propositions for testing the involvement construct in recreation tourism contexts. Leisure Sciences 12(2), 179-195. Holstein, J. A. & Gubrium, J. F. (2011). The constructionist analytics of interpretive practice. In N. K. Denzin & Y. S. Lincoln (eds.). The Sage Handbook of Qualitative Research, p. 341-358. Los Angeles: Sage Publications. Huang, Y. C., Backman, K. F., Backman, S. J. & Chang, L. L. (2015). Exploring the implications of virtual reality technology in tourism marketing: an integrated research framework. International Journal of Tourism Research, 18(2), 116=128. doi:10.1002/jtr.2038 Jeong, S. (2008). Collective production of public goods in online travel communities. Information Technology & Tourism, 10(4), 355-373. doi:10.3727/109830508788403141 Kounavis, C. D., Kasimati, A. E. & Zamani, E. D. (2012). Enhancing the tourism experience through mobile augmented reality: Challenges and prospects. International Journal of Engineering Business Management, 4, 1-6. doi:10.5772/51644 Korstanje, M. E. (2015). Críticas al concepto de realidad turística. Revista Turismo Estudos e Práticas, 4(2), 107-115. Korstanje, M. E. & George, B. P. (2015<a href="http://search.ebscohost.com/login.aspx?direct=true&profile=ehost&scope=site&authtype=crawler&jrnl=19415842&AN=102487305&h=Z8Bd3chXnDYhAXRgxRbRY3iB9yYFvlZj%2B%2FD%2FUDbPOOdLbTU1MuWV2ZalLQX5ONraPkicWviIR8pm%2Fo6rQMiFfA%3D%3D&crl=c">). Understanding the sociological roots of “no-shows” in technology mediated transactions in tourism. E-Review of Tourism Research , 11(6-5), 71–82. Lengkeek, J. (2001). Leisure experience and imagination. rethingking cohen’s modes of tourist experience. International Sociology, 16(2), 173-184. Lo, I. S. & McKercher, B. (2015). Ideal image in process: Online tourist photography and impression management. Annals of Tourism Research, 52, 104-116. doi:10.1016/j.annals.2015.02.019 MacCannell, D. (1973). Staged authenticity: Arrangements of social space in tourist settings. American Journal of Sociology, 79(3), 589-603. MacCannell, D. (1999). The Tourist: a new theory of the leisure class. Berkeley /Los Angeles: University of California Press. Mkono, M., Markwell, K. & Wilson, E. (2013). Applying Quan and Wang’s structural model of the tourist experience: A Zimbabwean netnography of food tourism. Tourism Management Perspectives, 5, 68-74. doi: 10.1016/j.tmp.2012.10.007 Molz, J. G. (2013). Social networking technologies and the moral economy of alternative tourism: The case of couchsurfing.org. Annals of Tourism Research, 43, 210-230. https://doi.org/10.1016/j.annals.2013.08.001 Munt, I. (1994). The Other’postmodern tourism: culture, travel and the new middle classes. Theory, Culture & Society. 11 (3), 101-123. Nava Jiménez, C., Castillo Nechar., M., Mendoza Valdés, R. & Vargas Martinez, E. E. (2014). La crítica en el pensamiento turístico. Rosa dos Ventos - Turismo e Hospitalidade, 6(3), 324-341. https://doi.org/10.4206/gest.tur.1998.n3-02 Neuhofer, B., Buhalis, D. & Ladkin, A. (2014). A typology of technology-enhanced tourism experiences. International Journal of Tourism Research, 16(4), 340-350. doi:10.1002/jtr.1958 Obenour, W., Patterson, M., Pedersen, P. & Pearson, L. (2006). Conceptualization of a meaning-based research approach for tourism service experiences. Tourism Management, 27(1), 34-41. doi:10.1016/j.tourman.2004.07.008 Oh, H. (2001). Revisiting importance-performance analysis. Tourism Management , 22(6), 617-627. Parasuraman, A., Zeithaml, V.A. & Berry, L.L. (1994). Alternative scales for measuring service quality: a comparative assessment based on psychometric and diagnostic criteria. Journal of Retailing, 70(3), 201-230. Pearce, P.L. (1988). The Ulysses Factor: evaluating visitors in tourist settings. New York: Springer Verlag. Pernecky, T. (2012). Constructionism. Critical pointers for tourism studies. Annals of Tourism Research, 39(2), 1116-1137. doi:10.1016/j.annals.2011.12.010 Priest, S. & Bunting, C. (1993). Changes in perceived risk and competence during whitewater canoeing. Journal of Applied Recreation Research, 18(4), 265-280. Quan, S. & Wang, N. (2004). Towards a structural model of the tourist experience: an illustration from food experiences in tourism. Tourism Management, 25(3), 297-305. doi:10.1016/S0261-5177(03)00130-4 Ryan, C. (1997). Rafting in the Rangitikei, New Zealand - An example of adventure holidays. En Getz, D. y Page, S. J. (Eds) The Business of Rural Tourism -International Perspectives. London: Wiley, 162-190. Ryan, C. (2003). Risk acceptance in adventure tourism- paradox and context. En Wilks, J. & Page, S.J. (Eds) Managing Tourist Health and Safety in the New Millennium. Oxford: Pergamon, 55-66. Ryan, C. y Gu, H. (2008). Destination branding and marketing: the role of marketing organizations. En Oh, H. (Ed) Handbook of Hospitality Marketing Management. Oxford: Butterworth Heinemann, 383-411. Ryan, C. (2010). Ways of conceptualizing the tourist experience a review of literature. Tourism Recreation Research, 35(1), 37-46. Secretaría de Desarrollo Turístico del Estado de Quintana Roo, México. (2014). Indicadores Turísticos. Sheldon, P. J. (2004). eTourism: information technology for strategic tourism management. Annals of Tourism Research, 31(3), 740-741. doi:10.1016/j.annals.2004.03.002 Small, J. (1999). Memory-work: a method for researching women’s tourist experiences. Tourism Management, 20(1), 25-35. doi:10.1016/S0261-5177(98)00091-0 Small, J. (2008). The absence of childhood in tourism studies. Annals of Tourism Research, 35(3), 772-789. doi:10.1016/j.annals.2008.06.002 Small, J., y Darcy, S. (2011). Understanding tourist experience through embodiment: The contribution of critical tourism and disability studies. In D. Buhalis & S. Darcy (Eds.), Accessible Tourism: Concepts and Issues. (1a, 73-97), London: Channel View Publications. Spolsky, B., Inbar-Lourie, O. & Tannenbaum, M. (2014). Challenges for Language Education and Policy: Making Space for People. New York: Routledge. Thurlow, C. & Jaworski, A. (2014). ‘Two hundred ninety-four’: Remediation and multimodal performance in tourist placemaking. Journal of Sociolinguistics, 18(4), 459-494. doi:10.1111/josl.12090 Traver, B. & Ryan, C. (2005). Destination image, romance and place experience- an application of intimacy theory in tourism. Tourism Management 26(4), 481-492. Tung, V. W. S., y Ritchie, J. R. B. (2011). Exploring the essence of memorable tourism experiences. Annals of Tourism Research, 38(4), 1367–1386. doi:10.1016/j.annals.2011.03.009 Tussyadiah, I. P. (2013). Toward a theoretical foundation for experience design in tourism. Journal of Travel Research, 53(5), 543-564. doi:10.1177/0047287513513172 Tzanelli, R. (2004). Constructing the ‘cinematic tourist’. The ‘sign industry’ of The Lord of the Rings. Tourist Studies, 4(1), 21-42. https://doi.org/10.4324/9780203940105 Tzanelli, R. (2006). Reel western fantasies: portrait of a tourist imagination in The Beach (2000). Mobilities, 1(1), 121-142. https://doi.org/10.1080/17450100500489296 Tzanelli, R., y Korstanje, M. E. (2016). Tourism in the European economic crisis: Mediatised worldmaking and new tourist imaginaries in Greece. Tourist Studies, 16(3), 296-314. https://doi.org/10.1177/1468797616648542 Uriely, N. (2005). The tourist experience. Conceptual developments. Annals of Tourism Research, 32(1), 199–216. doi:10.1016/j.annals.2004.07.008 Uriely, N., Yonay, Y. & Simchai, D. (2002). Backpacking experiences. A type and form analysis. Annals of Tourism Research, 29(2), 520-538. doi:10.1016/S0160-7383(01)00075-5 Urry, J. (2002). The tourist gaze. London: Sage Publications. Wang, N. (1999). Rethinking authenticity in tourism experience. Annals of Tourism Research, 26(2), 349-370. Wang, N. (2000). Tourism and modernity: A sociological analysis. Oxford: Pergamon. Wickens, E. (2002). The sacred and the profane. A tourist typology. Annals of Tourism Research, 29(3), 834-851. doi:10.1016/S0160-7383(01)00088-3 Yuan, Y.-L., Gretzel, U. & Fesenmaier, D. R. (2006). The role of information technology use in American convention and visitors bureaus. Tourism Management, 27(2), 326-341. doi:10.1016/j.tourman.2004.12.001 Yves, M. (2015). El nuevo lujo. Madrid: Taurus. RECEBIDO: 27 NOV 2016 AVALIADO: OUT - NOV APROVADO: 13 MAR 2017